PENGARUH KEDISIPLINAN, MOTIVASI DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR SANTRI DAYAH MASKANUL HUDA ACEH UTARA - Rizal, Saiful; Fauzi, Fauzi (IndOmera, 2023)
This study aims to examine and measure the influence of discipline, motivation and independence on the learning achievement of students at Dayah Maskanul Huda in the Keude Simpang area, Jalan Seunuddon, North Aceh Regency. This research is in the form of quantitative descriptive and associative methods with analysis techniques through the path model. The results showed that 1) there was a correlation between exogenous variables, namely the correlation of the variables of discipline and learning motivation of 0.508, the correlation of variables of learning motivation and learning independence of 0.364, the correlation of variables of learning independence and discipline of 0.445. 2) there is a direct and indirect effect of discipline on student achievement of 24,64%. 3) there is a direct and indirect effect of learning motivation on student achievement of 20.08%. 4) there is a direct and indirect effect of independent learning on student achievement of 30.51%. 5) Simultaneously discipline, learning motivation and learning independence make a positive contribution to student achievement by 57.7%. Meanwhile, the influence of other variables not examined was 42.3%.